First principle investigation of W/P3C sheet as an efficient single atom electrocatalyst for N2 and NO electrochemical reaction with suppressed hydrogen evolution. (15th January 2022) - Lin, Long; Yan, Longbin; Fu, Ling; He, Chaozheng; Xie, Kun; Zhu, Linghao; Sun, Jingwen; Zhang, Zhanying
Highlights: A series of transition metals are considered to be supported on P3 C sheet. The metals-substrate interaction can alter the local electronic structure. As a competitive reaction, hydrogen evolution reaction is suppressed on W/P3 C surface. Abstract: Electrocatalytic N2 reduction reaction (eNRR) and NO electroreduction reaction (NOER) are considered as the effective methods to synthesize NH3 under ambient conditions. Based on density functional theory, a series of transition metal atoms supported P3 C sheet is systematically investigated to screen out the most promising catalyst for eNRR and NOER. The results indicate that the W/P3 C could be an efficient single atom catalyst for eNRR and NOER with the limit potentials of −0.70 and −0.59 V respectively. Remarkably, W/P3 C is more conducive to eNRR and NOER than hydrogen evolution reaction. It can be concluded that the local geometric and electronic structure are altered due to the interaction between metal and support, which could promote eNRR and NOER. We hope this work could provide promising method to design the effective electrocatalyst.